Clinical implications of family history of prostate cancer and genetic risk single nucleotide polymorphism (SNP) profiles in an active surveillance cohort. (15th January 2013) - Goh, Chee L.; Saunders, Edward J.; Leongamornlert, Daniel A.; Tymrakiewicz, Malgorzata; Thomas, Karen; Selvadurai, Elizabeth D.; Woode‐Amissah, Ruth; Dadaev, Tokhir; Mahmud, Nadiya; Castro, Elena; Olmos, David; Guy, Michelle; et al.
Abstract : What's known on the subject? and What does the study add?: Family history (FH) is a major risk factor for the development of prostate cancer. The search for genetic variants has led to genome‐wide association studies (GWAS), which have so far reported 47 susceptibility loci that predispose men to prostate cancer. However, the use of genetics or FH status in predicting clinical outcomes after prostate cancer diagnosis remains uncertain. Guidelines currently exist for clinicians and patients summarising evidence relating to the best outcomes of different prostate cancer treatment methods. Genetics and FH could potentially add to this stratification. Our study aimed to ascertain the potential prognostic roles of FH or genetic risk scores in patients managed by active surveillance. Objectives: To explore the potential prognostic role of family history (FH) of prostate cancer and prostate cancer risk single nucleotide polymorphisms (SNPs) in patients undergoing active surveillance (AS) for prostate cancer. This is the first study to date, which has investigated the potential prognostic role of SNP profiles in an AS cohort Patients and Methods: FH data were collected from patients in the Royal Marsden Hospital AS study. In all, 39 prostate cancer‐risk SNPs identified from published genome wide association studies (GWAS) were genotyped using the Sequenom Platform and TaqMan™ assays from available DNA. The cumulative genetic‐risk scores for each patient were then calculated using the weighted effect estimated from previous GWAS (log‐additive model). FH status and the genetic‐risk scores were assessed against adverse outcomes in AS, time to treatment and adverse histology on repeat biopsy, using univariable and multivariable Cox regression models to address time to treatment; and binary logistic regression to address biopsy upgrade. Results: Of 471 patients, 55 (13.6%) had adverse histology on repeat biopsies and 145 (30.8%) had deferred treatment. On univariate analysis, there was no significant relationship between FH of prostate cancer in any degree of relation, and adverse histology or time to treatment. For risk score analyses, 386 patients' DNA was studied; and there was also no relationship found between the calculated genetic risk scores and adverse histology or time to treatment ( P = 0.573 and P = 0.965, respectively). The retrospective study design and the few events were the main limitation of the study. Conclusions: There is currently insufficient data to support the use of FH status or prostate cancer SNP profile risk scores as prognostic factors in AS and these should not be used to influence management decisions. As more genetic variants are discovered this may change and should be reassessed in multicentre AS cohorts.